2022
DOI: 10.1017/s0022377822000563
|View full text |Cite
|
Sign up to set email alerts
|

Direct computation of magnetic surfaces in Boozer coordinates and coil optimization for quasisymmetry

Abstract: We propose a new method to compute magnetic surfaces that are parametrized in Boozer coordinates for vacuum magnetic fields. We also propose a measure for quasisymmetry on the computed surfaces and use it to design coils that generate a magnetic field that is quasisymmetric on those surfaces. The rotational transform of the field and complexity measures for the coils are also controlled in the design problem. Using an adjoint approach, we are able to obtain analytic derivatives for this optimization problem, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…This finding is consistent with the fact that previous optimizations for QA at (NCSX and ARIES-CS) have had significant imperfections in the symmetry, whereas excellent QA has been obtained at (Giuliani et al. 2022; Landreman & Paul 2022). When , QA solutions were found that satisfied all constraints, but they resembled configurations that were translated or rotated to break two-field-period symmetry.…”
Section: Parameter Scanssupporting
confidence: 88%
“…This finding is consistent with the fact that previous optimizations for QA at (NCSX and ARIES-CS) have had significant imperfections in the symmetry, whereas excellent QA has been obtained at (Giuliani et al. 2022; Landreman & Paul 2022). When , QA solutions were found that satisfied all constraints, but they resembled configurations that were translated or rotated to break two-field-period symmetry.…”
Section: Parameter Scanssupporting
confidence: 88%
“…In the future, similar work could be pursued that considers windowpane coils to add primarily poloidal flux or attempts to achieve more than one type of quasisymmetry with a single coil set. Other formulations could be examined that incorporate objectives ensuring quasisymmetry to high order offaxis [16], target integrability on several surfaces throughout the plasma volume, or eliminate the need for an integrability objective by ensuring quasisymmetry on a given flux surface [28]. Stochastic optimization techniques could also be used to create coils that perform robustly even in the face of manufacturing errors [29].…”
Section: Discussionmentioning
confidence: 99%
“…the magnitude of the normal component n of the magnetic field induced by the coils on the boundary S. This is in contrast to the current carrying surface approach where coils are restricted to lie on a particular surface (called the coil winding surface) which is employed in the NESCOIL [33], REGCOIL [34], ONSET [35], COILOPT [3], and COILOPT++ [36] codes. The FOCUS approach implemented in SIMSOPT has been shown to yield exceptionally low field errors and allow for simple coil shapes (see [11,37]) and is therefore the one used here. We target the minimization of the field error by defining as a cost function the quadratic flux quantity f QF , given by…”
Section: Optimization Methodsmentioning
confidence: 99%
“…Previous combined optimization methods have either relied directly or indirectly on free boundary equilibrium calculations [3][4][5][6][7], which often demand many iterations between an equilibrium solution, or these can only be used with vacuum configurations [8][9][10][11][12]. In [13] several combined optimization approaches were discussed, including the possibility of using fixed boundary equilibria and the corresponding penalty functionals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation